On the uneven evolution of human know-how - Richard R. Nelson (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2002)
It is widely recognized that advances in knowhow have been the key driving force between the great improvements in human material well-being that have been achieved over the past two centuries. However, not much attention has been directed to the fact that the advances in knowhow that have been achieved have been highly uneven across different human wants. Thus advances in communications and computation technology have been dramatic. We have learned to eliminate or cure a wide variety of human diseases. Yet on the other hand, we have made little progress on certain kinds of diseases. And there has been very little progress on the processes of primary and secondary education. This paper explores the reasons behind the unevenness. Education is used as a canonical example of an area where little progress has been made. The analytic argument makes considerable use of a comparison between research and problem-solving in education, and research and problem-solving in various areas of medicine.
Keywords: 330; Know-How; Research; Problem-Solving; Humankapital; Wissen; Evolutionsökonomik; Theorie